Estimating the influence of age-related changes in skin stiffness on tactile perception for static stimulations - Toru HAMASAKI; Takahiro YAMAGUCHI; Masami IWAMOTO (Journal of Biomechanical Science and Engineering, 2018)
It is difficult to experimentally observe the influence of differences in individual skin properties of human fingers on tactile perceptions. During subjective experiments, many parameters, such as skin properties, the transmittance of nerve signals, and individual feelings are intricately mixed; therefore, it is difficult to identify which elements are affected and to what extent. It has not been determined how age-related changes in the stiffness of skin influence tactile perceptions. We developed a two-dimensional cross-section human fingertip finite element model based on previous studies. Then, we estimated the influence of age-related changes in skin stiffness on Merkel cells and tactile perceptions by using finite element analysis. Age-related changes in skin stiffness were described by changing skin material properties in the model. Simulations using a model involving the fingertip being contacted with a rigid flat plate or a 2-point indenter were performed. Using a rigid flat plate and standard skin material properties, the contact width between the finger pad and the object was 5 mm. Meanwhile, the width changed from 5 mm to 4 mm when using a model of age-related changes of skin. Using a rigid 2-point indenter, the difference in the peak-to-valley of the Mises distribution around the Merkel cells indicated 2-point discrimination. Besides, the difference decreased by approximately 43% with changes in skin stiffness. These results indicated that age-related changes in skin stiffness influenced tactile perceptions.